Parenting practices and children's dental caries experience: A structural equation modelling approach - Kumar, S.; Tadakamadla, J.; Zimmer‐Gembeck, M.J.; Kroon, J.; Lalloo, R.; Johnson, N.W. (Community dentistry and oral epidemiology, 2017)
Aim To evaluate the direct and mediated associations between parenting practices and dental caries experience in Indian school children. Methods The target population consisted of school children and their parents (N=1539) of Medak district in the state of Telangana, India. Parents completed a questionnaire that consisted of questions related to socioeconomic status (SES), family structure, the number of children, their own oral hygiene behaviour and parenting practices. Parenting practices were assessed using a translated version of the short form of Parent‐Child Relationship Questionnaire (PCRQ) which was found to have two factors, power assertion (ie over control and coercion) and positive parenting (warmth and positive parent‐child interaction). Children completed a questionnaire on tooth brushing frequency, dental visiting and sugar consumption practices to evaluate their oral hygiene behaviour, and underwent a clinical examination for dental caries by a single examiner. Path analysis was used to explore the influence of parent‐child relationship, SES and other family‐level variables on dental caries experience of children. Results Parents’ oral hygiene behaviour was positively (β=0.18, P=0.009), and power assertion negatively (β=−0.06, P=0.041) associated with children's oral hygiene behaviours. Families reporting higher SES had children with less dental caries experience (β=−0.10, P=0.028) and better oral hygiene behaviour (β=0.13, P=0.009). Power assertion parenting had an indirect association with dental caries experience (β=0.003, P=0.038). Conclusions Children had higher dental caries experience when they lived in families with lower SES and used more power assertion parenting practices.